The Legal Conflict In The Resolution of International Trade Disputes: A Comparison of Arbitration and Courts - Syahputra, Fajar; Neviyana, Erin; Syafaat, Muh. Nur; Dikrurrahman, Diky; Yusup Permana, Deni (Devotion : Journal of Research and Community Service, 2024)
International trade disputes often involve parties from different countries with different legal systems, resulting in legal conflicts in their resolution. This article aims to analyze the comparison between two commonly used dispute resolution mechanisms, namely arbitration and court. Through a normative juridical approach and comparative analysis, this study examines the advantages and disadvantages of both methods in the context of international law. Arbitration is often chosen because it is more flexible, confidential, and allows the parties to choose a competent arbitrator. In contrast, dispute resolution through the courts tends to be more formal, with clearer enforcement power but often takes longer and is less flexible. The results of this study show that arbitration is superior in terms of time efficiency and privacy, while courts are stronger in terms of law enforcement in various jurisdictions. The study concludes that the choice between arbitration and the court depends largely on the nature of the dispute at hand, the preferences of the parties, as well as the prevailing jurisdiction.